Form of Intimidation and Female Resistance in Eka Kurniawan’s Beauty is a Wound - Jurdi Yuda Pangestu; Muhammad Ali Pawiro (JOURNAL OF LANGUAGE, 2026)
This study examines the theme of intimidation and female resistance in the novel Beauty Is a Wound by Eka Kurniawan. It aims to identify the types of intimidation depicted in the novel and to analyze how the characters resist such intimidation. This research employs a qualitative descriptive method. The primary data source is the novel, published by Text Publishing Company in Melbourne in 2002, while data collection is conducted through note-taking techniques. The analysis is based on the classification of intimidation proposed by Coloroso and the theory of resistance by James C. Scott, supported by feminist theory as the main analytical framework. The findings reveal that the novel portrays several forms of intimidation, particularly verbal and physical intimidation. In response, the characters demonstrate open resistance, in which victims directly oppose discriminatory and oppressive treatment. The study shows that women are often portrayed as more vulnerable to intimidation due to persistent stereotypes of weakness. However, the novel also challenges this assumption by illustrating that women are capable of resisting intimidation and confronting injustice.